Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/pon.3638
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between age, anxiety, and depression in older adults with cancer

Abstract: Objective In older men with prostate cancer, aging is associated with reduced anxiety and increased depression. The purpose of this study was to examine the association among age, anxiety, and depression in a cohort of older adults receiving chemotherapy. Methods This is a secondary analysis of a prospective longitudinal study investigating chemotherapy toxicity in older adults with cancer. Baseline data (pre‐chemotherapy) included: age, sociodemographics, tumor and treatment factors, functional status, comorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
79
4
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 38 publications
15
79
4
12
Order By: Relevance
“…Several studies support our finding that medical comorbidities are associated with an increased prevalence of depression , most probably because of higher psychological burden.…”
Section: Resultssupporting
confidence: 85%
“…Several studies support our finding that medical comorbidities are associated with an increased prevalence of depression , most probably because of higher psychological burden.…”
Section: Resultssupporting
confidence: 85%
“…For example, studies found that individuals diagnosed at an advanced stage have a higher risk of developing depression compared with those diagnosed at an early stage. 5,14,15 Cancer treatment can also affect the risk of developing depression. Retrospective studies among women with breast cancer reported a significant association between chemotherapy treatment and the risk of depression.…”
Section: Introductionmentioning
confidence: 99%
“…In diesem Zusammenhang sind vor allem die Zunahme an Gebrechlichkeit, komorbiden kör-perlichen Erkrankungen, Funktionseinschränkungen, kognitiven Defiziten und Einschränkungen bei der Alltagsbewäl-tigung zu nennen [14,36]. Durch das gleichzeitige Auftreten mehrerer behandlungsbedürftiger Erkrankungen werden bei älteren Patienten oft mehrere Medikamente verordnet ("Polypharmazie"), deren Wechselwirkungen in der Regel schwer vorhersehbar sind.…”
Section: Psychosoziale Belastungsfaktoren Und Psychische Komorbiditätunclassified
“…Verschiedene Studien und Übersichts-arbeiten zeigen, dass bei älteren Krebspatienten Angststörungen und Depressionen zu den häufigsten psychischen Störungen zählen [11,19,36]. So werden bei bis zu 23% der älteren Krebspatienten Angststö-rungen berichtet.…”
Section: Psychosoziale Belastungsfaktoren Und Psychische Komorbiditätunclassified
See 1 more Smart Citation